The small parameter method for regular linear differential equations on unbounded domains - Karapetyan, Garnik; Tananyan, Hovhannes (Eurasian Mathematical Journal, 2013)
Algorithms for the asymptotic expansion of the solution to the Dirichlet problem for a regular equation with a small parameter \( ε \) (\( ε > 0 \)) at higher derivatives on an unbounded domain (the whole space, the half space and a strip), based on the solution to the degenerate (as \( ε → 0 \)) Dirichlet problem for a regular hypoelliptic equation of the lower order, are described. Estimates for remainder terms of those expansions are obtained.